(untitled) (American Journal of Islam and Society, 2013)
The opposition Islamist PAS (Parti Islam Se-Malaysia, or Pan Malaysian Islamic Party) is one of the oldest political parties in Malaysia. Inspired by Egypt’s Ikhwan al-Muslimin (Muslim Brotherhood [MB]), PAS is also influenced by occurrences in the Middle East; following the 1979 Iranian Revolution, its leaders revamped their organizational structure to entrust key decisions to religious scholars. The ramifications of the 2011 Egyptian revolution, arguably one of the most significant Middle Eastern political events in recent times, thus deserves a closer look. This short article attempts to look at this revolution’s possible impact on Islamists in Malaysia. I argue that Malaysia had already undergone its own version of a revolution in the 1998 reformasi (reformation) due to the shared characteristics between the two events: both (1) shared the same premise of alleged political injustice; (2) provided opportunities for Islamists to influence the political discourse, with the difference that in Egypt there was a political vacuum; and (3) utilized the Internet heavily to rally the masses. However, due to Malaysia’s freer democratic and electoral processes, political changes there will not be as abrupt as in Egypt. Furthermore, both Egypt’s revolution and Malaysia’s reformasi have hardly ended; the former is a tumultuous ongoing process of battling for the legitimacy of rule by appealing to the masses, while the latter is an ongoing process of appealing to voters in order to come to rule.